Tasawuf dalam Gerakan Dakwah Tanahair - Mohd Nasir, Badlihisham; Haji Talib, Othman (Jurnal Usuluddin, 2003)
It is undeniable fact that tasawwuf is one of the major aspect in Islam. It was not only the fact that tasawwuf has been practised as a ritual but also a factor in generating the spread of Islam. Sufi orders or movements all over the world said to be responsible in promoting da’wah although their understanding and practice of da’wah sometimes have been associated with such negative connotations like narrow-minded and backwardness. This issue particularly in the Malaysian context where there are needs to be addressed many da’wah movements engaged in da’wah. The essay attempts to highlight the association of tasawwuf with the Malaysian da’wah movements. In particular, it will critically discuss the understanding and practice of tasawwuf in these movements.